2000
DOI: 10.1590/s1516-35982000000200016
|View full text |Cite
|
Sign up to set email alerts
|

Estudo das associações genéticas entre perímetro escrotal e características reprodutivas de fêmeas Nelore

Abstract: RESUMO -Os objetivos deste trabalho foram estimar parâmetros genéticos para as características perímetro escrotal (PE), medido aos 12 (PE12, n = 652) e 18 (PE18, n = 607) meses de idade, idade ao primeiro parto (IPP, n = 1582), datas do primeiro (DPP, n = 1582) e segundo partos (DSP, n = 644) e primeiro intervalo de partos (PIP, n = 644) de animais da raça Nelore. Os parâmetros foram estimados pelo método da máxima verossimilhança restrita, usando-se um modelo animal e incorporando 15.648 informações de pedigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
3
48

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 20 publications
(8 reference statements)
7
15
3
48
Order By: Relevance
“…The heritability for SC of 0.53 6 0.04 (Table 3) was higher than those reported by Gressler et al (2000), Grossi et al (2008) and Frizzas et al (2009), who found estimates of 0.31, 0.46 and 0.42, respectively, for Nellore cattle at long YA. The heritability estimate for AFC (0.23 6 0.08) was higher than those reported by Boligon et al (2007) and Grossi et al (2008) for Nellore cattle (0.14 in both studies).…”
Section: Discussioncontrasting
confidence: 53%
“…The heritability for SC of 0.53 6 0.04 (Table 3) was higher than those reported by Gressler et al (2000), Grossi et al (2008) and Frizzas et al (2009), who found estimates of 0.31, 0.46 and 0.42, respectively, for Nellore cattle at long YA. The heritability estimate for AFC (0.23 6 0.08) was higher than those reported by Boligon et al (2007) and Grossi et al (2008) for Nellore cattle (0.14 in both studies).…”
Section: Discussioncontrasting
confidence: 53%
“…Na literatura não foi encontrado trabalho que fizesse esse tipo de diferenciação, de acordo com a idade à primeira exposição ao touro. Estudos com metodologias recentes na raça Nelore mostraram valores de herdabilidade para idade ao primeiro parto variando de 0,01 a 0,19 (Gressler et al, 1998;Dias et al, 2000 IPP14 (IPP26) = idade ao primeiro parto para fêmeas expostas ao touro pela primeira vez em torno de 14 (26) meses, DPP = dias para o parto, DG = duração da gestação, PE = perímetro escrotal, PESNAS = peso ao nascer, PESDES = peso à desmama, PESSOB = peso ao sobreano, GP345 = ganho de peso da desmama ao sobreano. a: O mesmo conjunto de dados em todas as análises.…”
Section: Resultsunclassified
“…O valor de herdabilidade para PE (0,46) está dentro da faixa de valores encontrada na literatura para a raça Nelore, de 0,31 (Gressler et al, 1998) a 0,77 (Quirino & Bergmann, 1998).…”
Section: Resultsunclassified
“…-E-mail: danisio@fcav.unesp.br Scrotal circumference (SC) measurements can also be used as selection criteria in programs aiming to improve production efficiency, since they present medium to high heritability (Quirino and Bergmann, 1998;Gressler et al, 2000;Pereira et al, 2000;Silveira et al, 2004) and favorable genetic associations with production traits (Moser et al, 1996;Cyrillo et al, 2001;Garnero et al, 2001) and reproductive traits (Martin et al, 1992;Gressler et al, 2000;Gianlorenço et al, 2003;Boligon et al, 2007). Furthermore, because SC is an easily measured trait and can be measured at young ages (weaning, 365 days of age and 550 days of age), this makes it possible to identify animals that are genetically superior in relation to these traits.…”
Section: Introductionmentioning
confidence: 99%